ASAS PUTUSAN HAKIM DALAM PERKARA PEREMPUAN BERHDAPAN DENGAN HUKUM DI INDONESIA: PERSPEKTIF CEDAW - Arrasyid, Fuazan; Harahap, Abdul Aziz (Institut Agama Islam Negeri Fattahul Muluk Papua, 2022)
Discriminatory treatment and gender stereotypes often adversely affect the accessibility of legal justice for women. This study aims to identify the dimensions of gender equality in the principle of judges' decisions contained in Supreme Court Regulation Number 3 of 2017 in the perspective of the Convention the Elimination of all Forms of Discrimination againt Women (CEDAW). This normative legal research uses a philosophical approach. The results of this study show that in terms of the CEDAW perspective, there is a mainstreaming of gender equality in various principles of judges' decisions on women's cases in Indonesia. First, the substantive dimension of equality in the principle of gender equality and equality before the law. Second, the dimension of non-discrimination in the principle of humanity and expediency. Third, the dimensions of state obligations in the principles of justice, non-discrimination and legal certainty.The theoretical implications of the findings of this study show various CEDAW principles have actually been manifested in various principles of judges' decisions on women's cases in Indonesia.